Socioeconomic Position and Age-Related Disparities in Regional Cerebral Blood Flow Within the Prefrontal Cortex. Issue 4 (May 2018) - Hackman, Daniel A.; Kuan, Dora C-H.; Manuck, Stephen B.; Gianaros, Peter J.
ABSTRACT: Objective: Socioeconomic position (SEP) is associated with cerebrovascular health and brain function, particularly in prefrontal cortex and medial temporal lobe regions that exhibit plasticity across the life course. However, it is unknown whether SEP associates with resting cerebral blood flow (CBF), an indicator of baseline brain function, in these regions in midlife, and whether the association is ( a ) period specific, with independent associations for childhood and adulthood SEP, or driven by life course SEP, and ( b ) explained by a persistent disparity, widening disparity, or the leveling of disparities with age. Methods: To address these questions, we analyzed cerebral perfusion derived by magnetic resonance imaging in a cross-sectional study of healthy adults ( N = 443) who reported on childhood and adult SEP. Main effects were examined as an index of persistent disparity and age by SEP interactions as reflecting widening or leveling disparities. Results: Stable high SEP across the lifespan was associated with higher global CBF and regional CBF (rCBF) in inferior frontal gyrus. However, childhood SEP was associated with rCBF in middle frontal gyrus, as moderated by age ( β = 0.04, p = .035): rCBF was inversely associated with age only for those whose parents had a high school education or below. No associations were observed for the hippocampus or amygdala. Conclusions: Life course SEP associations with rCBF in prefrontal cortex are suggestive of persistent disparities, whereas the age by childhood SEP interaction suggests that childhood disadvantage relates to a widening disparity, independent of global differences. These differential patterns in midlife may relate to disparities in later-life cerebrovascular and neurocognitive outcomes. Abstract : Supplemental digital content is available in the text.